2018
DOI: 10.1111/1365-2435.13031
|View full text |Cite
|
Sign up to set email alerts
|

Insect temperature–body size trends common to laboratory, latitudinal and seasonal gradients are not found across altitudes

Abstract: Body size affects rates of most biological and ecological processes, from individual performance to ecosystem function, and is fundamentally linked to organism fitness. Within species, size at maturity can vary systematically with environmental temperature in the laboratory and across seasons, as well as over latitudinal gradients. Recent meta‐analyses have revealed a close match in the magnitude and direction of these size gradients in various arthropod orders, suggesting that these size responses share commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…However, the head width was larger at 670 m than 800 m altitude, where the univoltine life cycle is expected to be maintained, as in other species of Orthoptera (Masaki ; Berner & Blanckenhorn ; Bidau & Martí ; Laiolo et al ; Eweleit & Reinhold ; Levy & Nufio ). Therefore, we conclude that the altitudinal variation in the head width was mainly resulted from the different lengths of the season available for growth, although lower temperature at higher altitudes might also be involved into the larger head width (Horne et al ). This altitudinal cline in the head width of P. mikado matches the expected pattern of the adult body size in insects that have variable voltinism (Roff ; Chown & Gaston ; Chown & Klok ).…”
Section: Discussionmentioning
confidence: 83%
“…However, the head width was larger at 670 m than 800 m altitude, where the univoltine life cycle is expected to be maintained, as in other species of Orthoptera (Masaki ; Berner & Blanckenhorn ; Bidau & Martí ; Laiolo et al ; Eweleit & Reinhold ; Levy & Nufio ). Therefore, we conclude that the altitudinal variation in the head width was mainly resulted from the different lengths of the season available for growth, although lower temperature at higher altitudes might also be involved into the larger head width (Horne et al ). This altitudinal cline in the head width of P. mikado matches the expected pattern of the adult body size in insects that have variable voltinism (Roff ; Chown & Gaston ; Chown & Klok ).…”
Section: Discussionmentioning
confidence: 83%
“…Bowden et al [26] found that habitat heterogeneity at finer scales overrides effects at broader scales in species with low mobility. In turn, Hein et al [27] and Horne et al [28] recently proposed that high mobility in a species might obscure reactions to environmental factors at finer scales.…”
Section: Introductionmentioning
confidence: 99%
“…Poikilotherms, however, frequently display a positive relationship between ambient temperature and body size, with smaller body sizes in cooler climates and larger body sizes in warmer climates (a 'converse-Bergmann pattern'; Mousseau 1997). Investigations of a broad range of insect taxa, however, reveal no uniform geographical body size pattern for poikilotherms (Shelomi 2012, Zeuss et al 2017, Horne et al 2018, and suggest that processes controlling body size may be fundamentally different for poikilotherms than for homeotherms.…”
Section: Introductionmentioning
confidence: 99%